„Baltijos skylė“ – sovietų blickrygas nuo Adutiškio iki Šiaulių (1944 m. liepos 5–31 d.) - Piličiauskas, Divonis (Vilnius University Open Series, 2025)
The article analyses and discusses the course of the Soviet ‘Šiauliai’ offensive operation until the stabilisation of the front line in Western Lithuania (5–31 July 1944). Based on archival documents, it looks at the clashes between the German and the USSR armies, the movement of troops, the precise tasks, and the losses incurred. The activity at the Second World War frontline in the territory of Lithuania in July 1944 were significant both for Lithuania and in the overall context of the Eastern Front, but this topic has hardly been explored in detail in historiography previously.